2009
DOI: 10.2176/nmc.49.565
|View full text |Cite
|
Sign up to set email alerts
|

Endorsement of the FOUR Score for Consciousness Assessment in Neurosurgical Patients

Abstract: The Full Outline of UnResponsiveness (FOUR) score was previously developed for neurological assessment, but has not been validated in neurosurgical patients, so was compared to the Glasgow Coma Scale (GCS) in practice. Four groups of raters, expert clinicians, novice clinicians, experienced nurses, and inexperienced nurses, assessed 64 patients in awake, drowsy, stuporous, and comatose conditions to investigate rater reliability. Then, 36 patients were evaluated by 1 expert clinician and 1 from the other group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
1
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 24 publications
6
33
1
9
Order By: Relevance
“…Pemeriksaan terhadap posisi tangan telah divalidasi sebelumnya dan dianggap reliabel untuk mendeteksi perubahan kesadaran sangat minimal. [13][14][15] Pemeriksaan refleks batang otak dapat membantu dalam penilaian kedalaman koma yang lebih lengkap dan akurat. Pemeriksaan fungsi batang otak, seperti refleks cahaya pupil, refleks kornea, dan refleks batuk dapat menilai fungsi mesensefalon, pons, medula oblongata, dan saraf okulomotor.…”
Section: Komponen Penilaian Pada Four Scoreunclassified
See 1 more Smart Citation
“…Pemeriksaan terhadap posisi tangan telah divalidasi sebelumnya dan dianggap reliabel untuk mendeteksi perubahan kesadaran sangat minimal. [13][14][15] Pemeriksaan refleks batang otak dapat membantu dalam penilaian kedalaman koma yang lebih lengkap dan akurat. Pemeriksaan fungsi batang otak, seperti refleks cahaya pupil, refleks kornea, dan refleks batuk dapat menilai fungsi mesensefalon, pons, medula oblongata, dan saraf okulomotor.…”
Section: Komponen Penilaian Pada Four Scoreunclassified
“…Refleks batuk hampir selalu menghilang bila refleks pupil dan kornea telah menghilang. 13 Pola napas Cheyne-Stokes dan ireguler dapat mencerminkan adanya disfungsi bihemisfer atau batang otak bagian bawah yang mengendalikan pernapasan, dan berhubungan dengan prognosis buruk. Pada pasien yang terintubasi, jumlah frekuensi napas yang melebihi frekuensi yang diberikan oleh mesin menggambarkan masih adanya fungsi pusat pernapasan atau usaha napas.…”
Section: Komponen Penilaian Pada Four Scoreunclassified
“…It was developed by Wijdicks et al, [4] and further validations of this scale were done by other researches. [5][6][7][8][9][10] It is composed of eye, motor, brainstem, and respiration responses with a scale of 0-4 (0=worst, 4=best) as demonstrated in Table 1. The FOUR score specifically distinguishes certain unconsciousness states, provides important details such as brainstem reflexes, and includes the minimal necessities of neurological testing in altered mental status.…”
Section: Sonuçmentioning
confidence: 99%
“…GCS components were unable to facilitate the assessment on patients with locked syndrome. 9,10 A new instrument was made to complete the GCS instrument which still has some shortcomings, and it is called Unresponsiveness Score (FOUR score).…”
Section: Introductionmentioning
confidence: 99%
“…The result of the study showed different sensitivity and specificity scores with different cut off score as well. 9,11,12 . An alternative instrument to assess level of consciousness is needed in order to fill the limitations of GCS components.…”
mentioning
confidence: 99%